The structures of CyMe4-BTBP complexes of americium(iii) and europium(iii) in solvents used in solvent extraction, explaining their separation properties. Issue 42 (1st October 2015) - Ekberg, Christian; Löfström-Engdahl, Elin; Aneheim, Emma; Foreman, Mark R. StJ.; Geist, Andreas; Lundberg, Daniel; Denecke, Melissa; Persson, Ingmar
Abstract : The structure around the absorbing atom in the dicomplexes of CyMe4 -BTBP of americium(iii ) and europium(III ) have been studied in solvent used in solvent extraction. Abstract : Separation of trivalent actinoid (An(iii )) and lanthanoid (Ln(iii )) ions is extremely challenging due to their similar ionic radii and chemical properties. Poly-aromatic nitrogen compounds acting as tetradentate chelating ligands to the metal ions in the extraction, have the ability to sufficiently separate An(iii ) from Ln(iii ). One of these compounds, 6, 6′-bis(5, 5, 8, 8-tetramethyl-5, 6, 7, 8-tetrahydro-benzol[1, 2, 4]triazin-3-yl)[2, 2]bipyridine, CyMe4 -BTBP, has proven to be resistant towards acidic environments and strong radiation from radioactive decomposition. EXAFS studies of the dicomplexes of CyMe4 -BTBP with americium(iii ) and europium(iii ) in nitrobenzene, cyclohexanone, 1-hexanol, 1-octanol and malonamide (DMDOHEMA) in 1-octanol have been carried out to get a deeper understanding of the parameters responsible for the separation. The predominating complexes independent of solvent used are [Am(CyMe4 -BTBP)2 (NO3 )] 2+ and [Eu(CyMe4 -BTBP)2 ] 3+, respectively, which are present as outer-sphere ion-pairs with nitrate ions in the studied solvents with low relative permittivity. The presence of a nitrate ion in the first coordination sphere of the americium(iii ) complex compensates the charge density of the complex considerably in comparison when only outer-sphere ion-pairs are formed as for the [Eu(CyMe4 -BTBP)2 ] 3+ complex. The stability and solubility of a complex in a solvent with low relative permittivity increase with decreasing charge density. The [Am(CyMe4 -BTBP)2 (NO3 )] 2+ complex will therefore be increasingly soluble and stabilized over the [Eu(CyMe4 -BTBP)2 ] 3+ complex in solvents with decreasing relative permittivity of the solvent. The separation of americium(iii ) from europium(iii ) with CyMe4 -BTBP as extraction agent will increase with decreasing relative permittivity of the solvent, and thereby also with decreasing solubility of CyMe4 -BTBP. The choice of solvent is therefore a balance of a high separation factor and sufficient solubility of the CyMe4 -BTBP ligand.